The Relationship between the Fear of Covid-19, Depression, and Spiritual Well-Being in Pregnant Women - Durmuş, Mustafa (Journal of religion and health, 2022)
The purpose of this study was to explore the relationship between pregnant women's fear of coronavirus (COVID-19), depression, and spiritual well-being. This cross-sectional research was carried out with 336 pregnant women living in a city in the Eastern Anatolia region of Turkey between the 1st of March and 30th of March 2021. For data collection, the scales of the Fear of COVID-19, the Beck Depression Inventory, and the Spiritual Well-being were administered to the participants. The pregnant women’s fear of COVID-19 was found to be at a moderate level, their depression was at a mild level, and their spiritual well-being was above the moderate level. It was found that there was a significant negative correlation between the spiritual well-being levels of pregnant women and their fear of COVID-19 and depression. Moreover, it was also found that there was a significant positive correlation between pregnant women’s levels of fear of COVID-19 and depression (p < 0.001). It is recommended that relevant spiritual care practices can be disseminated and implemented effectively to reduce pregnant women’s fear and depression during the pandemic. In addition, when providing care to pregnant women, health professionals can adopt a holistic approach to increase pregnant women’s spiritual well-being.